2006
DOI: 10.3168/jds.s0022-0302(06)72137-3
|View full text |Cite
|
Sign up to set email alerts
|

Plant Extracts Affect In Vitro Rumen Microbial Fermentation

Abstract: Different doses of 12 plant extracts and 6 secondary plant metabolites were incubated for 24 h in diluted ruminal fluid with a 50:50 forage:concentrate diet. Treatments were: control (no additive), plant extracts (anise oil, cade oil, capsicum oil, cinnamon oil, clove bud oil, dill oil, fenugreek, garlic oil, ginger oil, oregano oil, tea tree oil, and yucca), and secondary plant metabolites (anethol, benzyl salicylate, carvacrol, carvone, cinnamaldehyde, and eugenol). Each treatment was supplied at 3, 30, 300,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
282
7
20

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(350 citation statements)
references
References 37 publications
(60 reference statements)
41
282
7
20
Order By: Relevance
“…However, in a subsequent study by the same group (Busquet et al 2006), no changes in NH 3 concentration were observed when garlic oil was used at the same concentrations (3, 30, 300, and 3000 mg L…”
Section: Methanogenic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a subsequent study by the same group (Busquet et al 2006), no changes in NH 3 concentration were observed when garlic oil was used at the same concentrations (3, 30, 300, and 3000 mg L…”
Section: Methanogenic Activitymentioning
confidence: 99%
“…However, the increased pH was not accompanied by a significant decrease in total VFA concentrations although the later were numerically lower for treatments than for the control treatment. Results of the effects of EO and their compounds on total VFA concentration have been inconsistent depending on the type and the dosage rate of EO or EOC used (Busquet et al 2006). Nevertheless, in most studies, supplementation with EO or their compounds either decreased or had no effects on total VFA concentration.…”
Section: Methanogenic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In an experiment carried out on fattening lambs that consumed mixed feed with a blend of essential oil compounds having antioxidant activity, Ozdogan et al (2011) showed a slight improvement in BW and ADG, which could likely be due to the modification of rumen volatile fatty acid production by increasing the acetate-to-propionate ratio, inhibiting deamination, and the direct inhibition of methane production (Busquet et al, 2006;Castillejos et al, 2007). Corino et al (2007b) conducted a similar study on piglets in post-weaning; piglets were fed with a concentrate that was supplemented with two levels of VB, and the authors found considerable growth improvement in the subjects that were fed the highest level of VB.…”
Section: Productive Performancementioning
confidence: 99%
“…Results of these studies showed variable effects of essential oils and their derivatives on rumen bacteria and ruminal fermentation (Busquet et al 2006;Castillejos et al 2006). Discrepancies among studies were attributed to difference in type and doses of essential oils (Busquet et al 2006) and differences in technique used in these experiments .…”
Section: Introductionmentioning
confidence: 99%